Evaluation of PET Waste-Modified Asphalt Performance Under Environmental Stress: A Multi-Scale Analysis of Rheological and Durability Properties - Firmansyah Rachman; Cut Nawalul Azka; Tamalkhani Syammaun; Khairul Hamdi; T.M. Dandi (Elkawnie, 2025)
Abstract: Diesel fuel spills can significantly accelerate asphalt binder softening and mixture deterioration, leading to reduced pavement durability. This study applies a multi-scale evaluation framework to quantify the effectiveness of polyethylene terephthalate (PET) waste in mitigating diesel-induced degradation of asphalt by comparing conventional asphalt (0% PET, control) with PET-modified binders and mixtures containing 6% and 8% PET. The primary objective is to determine whether PET modification can enhance asphalt resistance to diesel contamination by examining the relationship between molecular-level stability, rheological response, and mixture-level performance, using standardized procedures in accordance with the Indonesian Bina Marga 2018 specification and relevant SNI and ASTM standards. The results indicate that diesel exposure causes severe degradation in the control binder, with non-recoverable creep compliance (Jnr) increasing by up to 62% after six hours, reflecting a substantial loss of resistance to permanent deformation. In contrast, PET-modified binders show markedly improved stability, with the 8% PET binder limiting the Jnr increase to approximately 51% under the same exposure, indicating the highest resistance to diesel-induced rheological deterioration. This improvement is consistently reflected at the mixture scale, where the control asphalt mixture experiences a 47% reduction in Marshall stability, while the mixture containing 8% PET shows only an 11% reduction after diesel conditioning. Overall, the findings demonstrate that PET waste—particularly at an 8% dosage—significantly enhances asphalt resistance to diesel-related chemical and mechanical damage. This study provides clear mechanistic and performance-based evidence that PET upcycling is an effective and sustainable strategy for producing more fuel-resistant asphalt pavements. Abstrak: Tumpahan bahan bakar diesel dapat secara signifikan mempercepat pelunakan aspal dan degradasi campuran aspal, sehingga menurunkan daya tahan perkerasan jalan. Penelitian ini menerapkan kerangka evaluasi multi-skala untuk mengkuantifikasi efektivitas limbah polyethylene terephthalate (PET) dalam mengurangi degradasi aspal akibat paparan diesel dengan membandingkan aspal konvensional tanpa PET (0% sebagai kontrol) dan aspal termodifikasi PET dengan kadar 6% dan 8%. Tujuan utama penelitian ini adalah untuk menilai kemampuan modifikasi PET dalam meningkatkan ketahanan aspal terhadap kontaminasi diesel melalui keterkaitan antara stabilitas molekuler, respons reologi, dan kinerja mekanis campuran, dengan menggunakan prosedur pengujian yang mengacu pada spesifikasi Bina Marga 2018 serta standar SNI dan ASTM yang relevan. Hasil penelitian menunjukkan bahwa paparan diesel menyebabkan degradasi yang signifikan pada pengikat kontrol, yang ditunjukkan oleh peningkatan nilai kepatuhan rangkak tidak pulih (Jnr) hingga 62% setelah 6 jam, menandakan penurunan ketahanan terhadap deformasi permanen. Sebaliknya, pengikat aspal termodifikasi PET menunjukkan stabilitas yang jauh lebih baik, di mana pengikat dengan 8% PET membatasi peningkatan Jnr hingga sekitar 51% pada kondisi paparan yang sama, sehingga memberikan ketahanan reologi tertinggi terhadap diesel. Peningkatan kinerja ini tercermin secara konsisten pada skala campuran, di mana campuran aspal konvensional mengalami penurunan stabilitas Marshall sebesar 47%, sementara campuran dengan 8% PET hanya mengalami penurunan sebesar 11% setelah pengkondisian diesel. Secara keseluruhan, hasil penelitian ini membuktikan bahwa pemanfaatan limbah PET—terutama pada kadar 8%—secara signifikan meningkatkan ketahanan aspal terhadap kerusakan kimia dan mekanis akibat paparan diesel. Temuan ini memberikan bukti mekanistik dan berbasis kinerja bahwa daur ulang PET merupakan strategi berkelanjutan yang efektif untuk menghasilkan perkerasan jalan yang lebih tahan terhadap kontaminasi bahan bakar.